Visi Deradikalisme Dalam Pendidikan Agama Islam Tentang Demokrasi di Universitas Samudra - Nurjanah, Nurjanah; Usman, Zulkifli Abdurrahman (Prodi Pendidikan Keagamaan Islam, 2023)
This article discusses Islamic Religious Education at Samudera University as an instrument of deradicalism. The aim of this article is to reveal the vision of deradicalism in the topic of democracy taught in Islamic religious education. Primary data is in the form of Islamic Religious Education modules and interviews with course lecturers. Data analysis uses qualitative descriptive methods and hermeneutic, historical, political, and Islamic theological approaches. The findings of this article show that Samudera University has a mission to support regional and national development, and Islamic religious education is an instrument of deradicalism. It was also found that deradicalism on the topic of democracy includes criticism of views that reject democracy in Islam; exploration of meaning, history, and values ​​in democracy; reveals the understanding that supports democracy in Islam, and the relevance of democracy to the history of classical Islamic political praxis. Based on these findings, it is concluded that Islamic religious education regarding democracy at Ocean University not only has a vision of deradicalism, but also functions to build harmony between religious beliefs and empirical social problems.